Isolation and bio-estimation of toxin from different isolates of Alternaria solani the causal of early blight disease of tomato in Al-Gabal Al-Akther district - Mohamed, Nwara A.; Saeed, Mohammed A.; El-Samman, M.G.; Abugharsa, Issa A. (Al-Mukhtar Journal of Sciences, 2002)
This study was conducted in the faculty of Agriculture in the University of Omar Al-Mukhtar (GSPLAJ). The study aimed to isolate the toxins from different isolates of Alternaria solani and bio-estimation of these toxins. Seven isolates from the mention fungus was collected from different Locations of Al-gabal Al-Akhdar district included (Derna, Elbedia and El-Marg). Crystal of Alternaric acid was obtained in pure case from these isolates. The results indicated that there were significant differences between isolates in their capability to produce the toxin that isolated on TLC and there was a different in the quantity of the produced toxin, according to the used cultural media, inoculation of tested tomatoes leaves with fungal spore gives the ideal symptoms while the tested toxins gives only discoloration of the tested leaves. The raw toxin and fungal filtrates cause decreases in the germination of tomato seeds and the length of the rootlettes indicated that the toxin is not from primary determinant group.